2006
DOI: 10.1007/s00264-006-0188-6
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous endoscopic discectomy and drainage for infectious spondylitis

Abstract: Fifteen patients with infectious spondylitis were treated by percutaneous endoscopic discectomy and drainage (PEDD) and associated appropriate parenteral antibiotics. Infectious spondylitis was diagnosed clinically, on the basis of elevated erythrocyte sedimentation rate (ESR) and Creactive protein (CRP) values, and on roentgenographic and magnetic resonance imaging (MRI) findings. Causative bacteria were identified in 13 (86

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 24 publications
0
44
0
1
Order By: Relevance
“…The positive culture rate was comparable to that obtained with open biopsy and superior to that of the CT-guided biopsy group. The size of the biopsy needle or discectomy forceps determines the sample size, which correlates to the positivity of the culture rate [2,6,22]. A sufficient amount of specimen can be obtained through PEDD with the patient under local anesthesia, avoiding the potential morbidity associated with an extensive surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive culture rate was comparable to that obtained with open biopsy and superior to that of the CT-guided biopsy group. The size of the biopsy needle or discectomy forceps determines the sample size, which correlates to the positivity of the culture rate [2,6,22]. A sufficient amount of specimen can be obtained through PEDD with the patient under local anesthesia, avoiding the potential morbidity associated with an extensive surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous endoscopic discectomy and drainage (PEDD), a relatively new technique, is emerging because of its simplicity and apparent diagnostic accuracy from 45% to 87% according to the organism isolated [10,13,22].…”
Section: Introductionmentioning
confidence: 99%
“…Delay in appropriate treatment for spinal infections can further lead to structural instability, spinal deformity, sepsis, neurologic deficit, and even death. The efficacy of PELD in terms of its diagnostic and therapeutic value has already been reported in several studies [13][14][15]. Most of these studies emphasized the importance of earlystage infection control, which usually leads to satisfactory outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…However, the continuous irrigation restrained the patients to their beds and limited their postoperative ambulation and activities. The diagnostic and therapeutic value of percutaneous endoscopic lavage and drainage (PELD) has already been proved in some recent studies [13][14][15]. However, most of these studies focused on the effect of PELD in early-stage infection.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, Ito et al [17] and Yang et al [18] reported the results of percutaneous endoscopic discectomy and drainage (PEED) applied to 15 cases (30 cases in total). Ito et al conducted a detailed evaluation of pain alleviation using a visual analog scale (VAS, 0-100mm).…”
Section: Discussionmentioning
confidence: 99%